Meningkatkan Kompetensi Literasi Al-Qur'an melalui Pendekatan Inovatif di Pondok Pesantren Al-Izzah Kota Batu: Improving Al-Qur'an Literacy Competency through an Innovative Approach at the Al-Izzah Islamic Boarding School, Batu City - Murdiono, Murdiono (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
This community service program aims to enhance the literacy competence of the Quran at Al-Izzah Islamic Boarding School in Kota Batu through an innovative approach to strengthen the scholarly foundation of the students. The methods employed involve workshops and training for educators, the development of technologically-based teaching materials, and the implementation of active learning activities. Evaluation encompasses aspects of comprehension, memorization of sacred verses, and Quranic reading skills. The results reflect a significant improvement in all aspects, with a high level of satisfaction from the boarding school authorities. The program successfully establishes an adaptive and responsive learning environment to contemporary developments, ensuring that students not only possess a strong Quranic literacy but can also apply Islamic teachings in a modern context. In conclusion, the innovative approach proves to be an effective solution in reinforcing Quranic literacy and scholarly knowledge among students at Al-Izzah Islamic Boarding School in Kota Batu.